Toward a Theory of Emotions in Competitive Sports - Jekauc, Darko; Fritsch, Julian; Latinjak, Alexander T. (Frontiers in Psychology, 2021)
In this article, we introduce a theory on the dynamic development of affective processes, affect regulation, and the relationship between emotions and sport performance. The theory focusses on how affective processes emerge and develop during competitive sport involvement. Based on Scherer's component process model, we postulate six components of emotion that interact with each other in a circular fashion: I) triggering processes, II) physiological reactions, III) action tendencies, IV) expressive behaviors, V) subjective experience and VI) higher cognitive processes. The theory stresses the dynamics of affective processes and describes the consequences for performance in competitive sports. It assumes that the peculiarities of different sports must be taken into account in order to understand the affective processes, and offers starting points on which strategies can be used to effectively regulate affective states. Consequences for research and practice are derived and discussed. To study the development of affective processes, future research should test the assumptions in ecologically valid contexts, such as real competitions or competition-like situations, using multi-component measures of emotions.